INVESTIGATION OF THE PROPERTIES OF CONCRETE BASED ON NON-FIRING ALKALINE BINDERS - Adxamjon Khamidov,Islombek Akhmedov,Yusupov Shavkat,Zayniddin Jalalov,Isroiljon Umarov,Sodiqjon Xakimov,Akbarjon Abdunazarov (Journals Park Publishing, 2022)
The article deals with the use of film-forming materials for the care of freshly laid concrete based on non-firing alkaline binders, the results of studies to determine the strength, frost resistance and plastic shrinkage of concrete are presented.
Keywords: Concrete, unfired alkaline binder, fresh concrete care, film-forming materials, strength, frost resistance, plastic shrinkage.